Penerapan Algoritma Apriori pada Sistem Informasi Inventori Toko - Muhammad Ulil Albab; Deny Hidayatullah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
In this contemporary era, meals wishes are a vital want for all people, a variety of commercial enterprise companies that sell their products are coming and growing quite significantly, besides that, dynamic web users in this country are growing quite rapidly every year. Resulting in business actors competing with each other to explore various technical options in terms of data processing to find out information on the availability of incoming goods and goods sold. In this study, a business still uses a manual system here and a computerized system will be created to assist business people in processing goods data in their business, then obtain information related to inventory and profit income. This web-primarily based totally stock statistics device additionally applies apriori information mining to decide income styles on the way to later grow to be patron advice statistics. The results obtained in this study are the creation of a web-based inventory information system by applying apriori data mining aimed at Toko Tri.